Proudly we can be Africans : Black Americans and Africa, 1935-1961 - Meriwether, James Hunter, 1963- (John Hope Franklin series in African American history and culture., 2002)
In the mid-20th century nations across Africa fought for their independence from colonial forces. By examining black Americans' attitudes toward and responses to these struggles, this work probes the shifting meaning of Africa in the intellectual, political and social lives of African Americans.